The association of hypotension during non‐cardiac surgery, before and after skin incision, with postoperative acute kidney injury: a retrospective cohort analysis. (24th August 2018) - Maheshwari, K.; Turan, A.; Mao, G.; Yang, D.; Niazi, A. K.; Agarwal, D.; Sessler, D. I.; Kurz, A.
Summary: Intra‐operative hypotension is associated with acute postoperative kidney injury. It is unclear how much hypotension occurs before skin incision compared with after, or whether hypotension in these two periods is similarly associated with postoperative kidney injury. We analysed the association of mean arterial pressure < 65 mmHg with postoperative kidney injury in 42, 825 patients who were anaesthetised for elective non‐cardiac surgery. Intra‐operative hypotension occurred in 30, 423 (71%) patients: 22, 569 (53%) patients before skin incision; and 24, 102 (56%) patients after incision. Anaesthetised patients who were hypotensive had mean arterial pressures < 65 mmHg for a median (IQR [range]) of 5.5 (0.0–14.7 [0.0–60.0]) min.h −1 before skin incision, compared with 1.7 [0.3–5.1 [0.0–57.5]) min.h −1 after incision: a median (IQR [range]) of 36% (0%–84% [0%–100%]) of hypotensive readings were before incision. We diagnosed postoperative kidney injury in 2328 (5%) patients. The odds ratio (95%CI) for acute kidney injury was 1.05 (1.02–1.07) for each doubling of the duration of hypotension, p < 0.001. Postoperative kidney injury was associated with the product of hypotension duration and severity, that is, area under the curve, before skin incision and after, odds ratio (95%CI): 1.02 (1.01–1.04), p = 0.004; and 1.02 (1.00–1.04), p = 0.016, respectively. A substantial fraction of all hypotension happened before surgical incision and was thus completely due to anaesthetic management. We recommend that anaesthetists should avoid mean arterial pressure < 65 mmHg during surgery, especially after induction, assuming that its association with postoperative kidney injury is, at least in part, causal.